1985
DOI: 10.1161/01.cir.72.4.825
|View full text |Cite
|
Sign up to set email alerts
|

Fetal atrioventricular valve insufficiency associated with nonimmune hydrops: a two-dimensional echocardiographic and pulsed Doppler ultrasound study.

Abstract: Of 466 fetuses who underwent cardiac ultrasound examination with cross-sectional and M mode echocardiography and pulsed Doppler ultrasound and in whom we were able to follow the natural history, 12 were found to have atrioventricular valve insufficiency and nonimmune hydrops. Eleven fetuses (all of whom had structural heart disease) died either in utero or during the early postnatal period. In the one surviving hydropic fetus with supraventricular tachyarrhythmia and atrioventricular valve regurgitation but wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(23 citation statements)
references
References 26 publications
0
22
1
Order By: Relevance
“…In the fetus, TR fre quently coincides with hydrops and the in crease in cardiac overload due to TR can itself lead to hydrops [13]. Indeed, all of group 1 showed both TR and high PLI val ues.…”
Section: Discussionmentioning
confidence: 94%
“…In the fetus, TR fre quently coincides with hydrops and the in crease in cardiac overload due to TR can itself lead to hydrops [13]. Indeed, all of group 1 showed both TR and high PLI val ues.…”
Section: Discussionmentioning
confidence: 94%
“…[7,20], Therefore, the application of all meth ods of fetal echocardiography is essential in the antenatal diagnosis and management in presence of NIHF [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigators reported that lung hypoplasia secondary to cardiomegaly, pleural effusion, or both in utero is the main cause for the high death rate in this disease [3,7]. However, it is noteworthy that the histologic features of the lungs in patients with lung hypoplasia and significant tricuspid valve disease diagnosed in utero or in the early neonatal period were normal [4], and a real reduction in the number of airway branches has been seen when the condition originates before 17 weeks' gestation [9].…”
Section: Discussionmentioning
confidence: 99%